Unveiling the Industry and Academia Gap in the Nepalese Hospitality Industry - Dinesh Basnet; Roopesh Shrestha (Management Dynamics, 2024)
This study aims to explore the gap between industry and academia in the Nepalese hospitality industry and identify the root cause factors to mitigate this gap. An exploratory research design has been used in this study. Semi-structured interviews were conducted with employees from the hospitality industry. The study sample consisted of seven employees from the hospitality sector using a convenience and purposive sampling method. Thematic analysis was utilized to identify the sub-themes and themes. The findings show that graduates are not adequately prepared regarding knowledge, ability, attitude, industry-specific trends and development skills (industry-academia expectation gap), communication and critical thinking, collaboration between academia and industry, and resource constraints are the significant gaps identified between industry and academia. This study emphasizes the collaborative engagement of industry and academia to bridge the industry-academia gap. Based on the findings of this study, academia and industry might work together to strengthen the identified key factors and reduce the gap between them. Further, this study fills the gap between industry and academia in the Nepalese hospitality industry and adds value to theoretical and empirical knowledge.